Laparoscopic gastrectomy for gastric cancer with two left gastric arteries: Safe and adequate lymphadenectomy in a rare arterial abnormality. Issue 1 (20th July 2022) - Ito, Sunao; Ogawa, Ryo; Saito, Masaki; Ueno, Shuhei; Hayakawa, Shunsuke; Okubo, Tomotaka; Sagawa, Hiroyuki; Tanaka, Tatsuya; Takahashi, Hiroki; Matsuo, Yoichi; Takiguchi, Shuji
Abstract: Clinical studies have established the safety and advantages of laparoscopic surgery for gastric cancer; therefore, laparoscopic gastrectomy (LG) in clinical practice is increasing. We report the case of a 77‐year‐old patient with gastric cancer who was referred to our center for LG. Esophagogastroduodenoscopy revealed a type 3 tumor identified as adenocarcinoma on biopsy. Three‐dimensional computed tomography‐angiography revealed two left gastric arteries (LGAs) branching from the celiac trunk. By laparoscopically performing the outermost layer‐oriented lymphadenectomy (OML‐OL), the two LGAs were detected and appropriately divided. Subtotal gastrectomy was completed, and the patient had an uneventful postoperative course. The OML‐OL was appropriate for LG in this situation. This case demonstrates the necessity of preoperative three‐dimensional computed tomography‐angiography with 1‐mm slices and the importance of performing OML‐OL.